Freezing copper as a noble metal–like catalyst for preliminary hydrogenation - Sun, Jian; Yu, Jiafeng; Ma, Qingxiang; Meng, Fanqiong; Wei, Xiaoxuan; Sun, Yannan; Tsubaki, Noritatsu (Science advances, 2018)
Copper is “frozen” into a metallic state as a noble metal–like catalyst for controlling the product in a chemical reaction. The control of product distribution in a multistep catalytic selective hydrogenation reaction is challenging. For instance, the deep hydrogenation of dimethyl oxalate (DMO) is inclined to proceed over Cu/SiO 2 catalysts because of inevitable coexistence of Cu + and Cu 0 , leading to hard acquisition of the preliminary hydrogenation product, methyl glycolate (MG). Here, the oriented DMO hydrogenation into MG is achieved over the sputtering (SP) Cu/SiO 2 catalysts with a selectivity of more than 87% via freezing Cu in a zero-valence state. Our density functional theory calculation results revealed that Cu 0 is the active site of the preliminary hydrogenation step, selectively converting DMO to MG via •H addition, while Cu + is a key factor for deep hydrogenation. The prominent Coster-Kronig transition enhancement is observed over SP-Cu/SiO 2 from Auger spectra, indicating that the electron density of inner shells in Cu atoms is enhanced by high-energy argon plasma bombardment during the SP process. Thus, the “penetration effect” of outermost electrons could also be enhanced, making these Cu nanoparticles exhibit high oxidation resistance ability and present noble metal–like behaviors as Au or Ag. Therefore, the regulation of Cu chemical properties by changing the electron structure is a feasible strategy to control the hydrogenation products, inspiring the rational design of selective hydrogenation catalysts.